Exploring Determinant Factors on Indonesian MSMEs Financing in Sharia Banking - Angga Dwi Febrianto; Ibnu Soleh; Mochlasin Mochlasin (Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Negeri (IAIN) Salatiga, 2022)
This study aims to determine the effect of CAR and NPF on Murabahah Financing with ROA as an Intervening variable at Indonesian Islamic Banks. This study uses quantitative methods with secondary data. The sample used as the object of research is 12 Islamic Commercial Banks. The sampling technique in this research is purposive sampling. The analytical tool used is eviews9. The test results regarding CAR have a negative and insignificant effect on MSME financing. NPF has a positive and significant effect on MSME financing. CAR) has a positive and insignificant effect on ROA. NPF has a negative and significant effect on ROA. ROA has a positive and significant effect on ROA. The ROA variable can mediate the CAR on Murabahah Financing not significantly. ROA cannot mediate the NPF on Murabahah Financing significantly.